Metabolic and physiological traits of bambara groundnut (vigna subterranea (L.) Verdc) in irrigated and drought conditions - Cleasby, Philip Michael (2019)
Bambara groundnut (Vigna subterranea (L.) Verdc) is an underutilised crop grown under rain fed conditions in Africa where drought is a major limiting factor for crop production. Many reports have described Bambara groundnut as a drought resistant crop, however limited evidence exists on the particular extent of resistance and the specific traits and physiological processes that enable it to resist drought relative to other important leguminous crops. The review paper provides a comprehensive summary of the main lessons learned about Bambara groundnut’s drought tolerance, the potential of Bambara groundnut to provide food security in the face of climate change and offers insights for the direction of future research that will allow its potential to be realised in the changing African climate. The first study was carried out to investigate and gain insights into the physiological responses of two landraces of Bambara groundnut to water stress, including above ground and below ground traits. Plants were grown in PVC columns to allow for sufficient root growth and to ensure a more realistic growing environment. Drought conditions were imposed during late reproductive stages of development. Physiological measurements were taken on site throughout the study with root analysis and yield parameters taken at final harvest. Roots were removed from columns and separated from the stem of the plant before being analysed using root scanning software. Overall stomatal conductance decreased in both landraces as a result of drought, whereas chlorophyll content showed no signs of decrease. Burkina maintained greater above ground biomass in both treatments, with higher leaf number, canopy spread, plant height and chlorophyll content throughout, however results suggest this was at the expense of pod production. Nav 4 showed signs of pod formation up to 1 week before Burkina in the irrigated treatment and had significantly more pods under the drought treatment, possibly as a result of its faster development rate allowing it to avoid the onset of drought. Root analysis showed Burkina had a greater surface area and root length in both treatments, with significant longer roots in the drought treatment, possibly allowing it to maintain water availability and ensure above ground plant growth. The second experiment built on these findings by repeating a similar experiment with larger columns, with drought exposed for a longer period of time and with metabolic assessments. It was expected that drought would lead to a significant change in the characteristics being observed, and that the more drought tolerant landraces would exhibit show a larger root surface area and taproot length and an increase in the biochemical parameters being observed. The hypotheses are shown in greater detail in the following section. The landrace TVSU89 displayed the highest yield under drought conditions, alongside a reduction in leaf and shoot biomass, higher stomatal conductance and chlorophyll content, reduced root surface area and a greater concentration of anthocyanin. The findings of this work point to further column-based research in more tightly controlled conditions to investigate some of these parameters in more detail.